2021
DOI: 10.4018/jgim.20211101.oa51
|View full text |Cite
|
Sign up to set email alerts
|

Using Customer Review Systems to Support Purchase Decisions

Abstract: Online reviews have emerged as influential sources of information which greatly affect customers’ pre-purchase decision. Some studies have found that culture impacts online reviews, but many aspects of online review usage are still not well-understood. This study seeks to understand: What factors influence the usage of online reviews and consumers’ intention to use online reviews influenced by culture? This study collects data from U.S. and Thai consumers to examine what factors affect user attitudes and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The rapid growth of mobile payments in developing countries and the rapidly changing mobile technologies can easily render previous studies out-of-date, as new factors become more important to consumers in their decision to utilize mobile payments. Many studies have shown that cultural differences among countries can influence the decision to accept new technology (Changchit et al, 2018;Changchit et al, 2021;Lonkani et al, 2020). Therefore, the factors affecting mobile payment acceptance shown in the context of developed countries need to be tested empirically in the contexts of developing and newly emerging countries, which are experiencing rapid technological growth, to see whether their effects are consistent.…”
Section: Research Gap and Study Contributionsmentioning
confidence: 99%
“…The rapid growth of mobile payments in developing countries and the rapidly changing mobile technologies can easily render previous studies out-of-date, as new factors become more important to consumers in their decision to utilize mobile payments. Many studies have shown that cultural differences among countries can influence the decision to accept new technology (Changchit et al, 2018;Changchit et al, 2021;Lonkani et al, 2020). Therefore, the factors affecting mobile payment acceptance shown in the context of developed countries need to be tested empirically in the contexts of developing and newly emerging countries, which are experiencing rapid technological growth, to see whether their effects are consistent.…”
Section: Research Gap and Study Contributionsmentioning
confidence: 99%
“…These perceptions extend onto the scope of this research study. Across different cultures, reactions to online reviews and perceptions of online reviews can differ despite similar messaging (Ali et al, 2021;Changchit et al, 2021). Individuals from cultures that accept power distance agree more to an inherent social distance between individuals compared to people coming from a dissimilar level of social hierarchy.…”
Section: Cross-cultural Findingsmentioning
confidence: 99%
“…Based on the dataset collected from related government departments and authoritative research institutions, the authors determined the postgraduate education institutions' location (in [latitude, longitude] format) with the help of the Baidu Maps development platform. 2 Following the Geographic Information System (GIS) approach (Changchit et al, 2021;Gallego-Gomez et al, 2021;Huang et al, 2021;Kesharwani et al, 2021;Lee et al, 2021;Peng, Chen et al, 2021;Srivastava & Eachempati, 2021;Xanthidis & Xanthidou, 2021;ZareRavasan, & Krčál, 2021;, the authors quantitatively explore the spatial aggregation characteristics of postgraduate education in China, using ArcGIS software and related tools or documents, at three scales: the comprehensive economic zone, the provincial, and the city scale. Second, the authors follow the social and economic geography viewpoint to quantitatively explore factors that may influence the spatial development pattern of China's postgraduate education.…”
mentioning
confidence: 99%